The collected stories of Gregorio C. Brillantes - Brillantes, Gregorio C. (Ateneo de Manila University Press, 2023)
Gathered in this book are stories that bear witness to half a century of postwar life in the Philippines: A country doctor reckons with mortality after seeing a dying infant. A young boy fears the end of days on his way home from the movies. Friends throw parties to discuss dictatorships and insurgencies over bottles of whiskey. Meanwhile, a family besieged by rising floodwaters faces a more menacing threat.